MiniPIX Timepix3 — a miniaturized radiation camera with onboard data processing for online characterization of wide-intensity mixed-radiation fields. (1st March 2022) - Granja, C.; Jakubek, J.; Soukup, P.; Jakubek, M.; Turecek, D.; Marek, L.; Oancea, C.; Gohl, S.; Bergmann, B.; Pospisil, S.; Malich, M.; Vuolo, M.; et al.
Abstract: The miniaturized radiation camera MiniPIX TPX3 is designed for detailed and wide-range measurements of mixed-radiation fields present in many applications such as radiotherapy and space radiation in outer orbit. The highly integrated instrumentation utilizes a single connector for control and readout for flexible measurements and quick deployment. The device features an option to process the registered data on the same device with limited resolution and basic particle-type resolving power. A novel readout and data processing technique exploits the detector high granularity and double per-pixel signal electronics to measure and characterize radiation fields of high intensity over a wide range with basic particle-type discrimination.